FBM business solutions / Fatin Umiera Rohaizan … [et al.] - Rohaizan, Fatin Umiera; Md Hashim, Mohammad Hafizee; Ariffin, Muhammad Fuad; Razali, Muhammad Zaid; Syed Amran, Syed Zul Hafiz (2017)
FBM Business Solutions operates in Malaysia's cleaning industry which contribute approximately. The demand for cleaning services is expected to increase further to RM100 million at the end of 2018. With these figures, FBM Business Solutions that established since 2014 and still quite new in the business believes that the business have the opportunities to grow in the market in the future. The owner believes that his goals on having own brand and label will be achieved.